Desain Pengembangan Buku Ajar Bahasa Arab Berbasis Permainan Edukatif untuk Meningkatkan Keterampilan Menulis - Lailatul Mathoriyah; Aufia Aisa; Bela Rachmadania Nabilla (LPPM Universitas KH. A. Wahab Hasbullah, 2022)
This research is motivated by the lack of MA Balongrejo Sumobito students in mastering Arabic writing skills so that it affects the low interest and learning achievement. This is because conventionally which ultimately causes students to tend to be passive and get bored quickly in learning Arabic. Therefore, this study aims to develop a textbook based on Arabic language skills educational games as a solution to overcome the lack of proficiency in writing Arabic for students. The method used in this research is R&D by adopting the ADDIE model. The subjects in this study were students of class X MA Balongrejo Sumobito, totaling 27 children. Data collection instruments used in the form of interviews, questionnaires and tests. The types of data analyzed produce qualitative and quantitative data including: 1) teaching materials have been developed in the form of Arabic textbooks based on Arabic vocabulary and sentence educational games. 2) based on the validity test, the textbook developed reached a very valid feasibility level with an average of 93.33% from material experts and 83.57% from media experts. 3) the level of effectiveness of the textbooks is very effective, seen from the comparison of the pre-test scores reaching an average of 40.74% and the post-test reaching an average of 77.77%.